PRINCIPLE OF OPERATION OF A MECHANICAL INERTIAL IMPULSE DRIVE - Zhurylenko, Borys (Science-based technologies, 2025)
For the movement of spacecraft with astronauts in outer space over long distances, efficient systems of engines and thrusters are needed to accelerate the apparatus to the required speeds. This, accordingly, will reduce the time astronauts spend in conditions where there is radiation and other harmful effects on their health, and will reduce the flight time. Reusable aerospace systems have long seemed like a promising replacement for rockets. However, it is still impossible to create a ship and organize manned interstellar flights at all. At the moment, there are many unsolved problems, one of which is the problem of choosing an engine. There is a pseudoscientific concept related to inertial propulsion and has two opposing opinions: one indicates that such an engine in a closed system (for example, a spacecraft) cannot be built, and the second, on the contrary, it is possible, and models operating in terrestrial conditions are given, the action of which is not always clearly explained. I would like this problem to be solved from a scientific point of view. But, if the pseudoscientific concept of an inertial propulsion system is wrong and it is possible to build such a system, then it would solve some problems associated with flights, both in space and on Earth. If such a system were available, it would be possible to create an ideal spacecraft that would use an electric motor and a pulse mechanical inertial propulsion system. Solar panels or an electric generator powered by a nuclear reactor could be used as a long-term source of electrical energy to power the electric motor. The mass of the spacecraft will practically not change during the flight. The purpose of the article is to theoretically show or refute the possibility of creating a mechanical inertial propulsion system for flights in outer space and on Earth. The paper theoretically considers the possibility of building a pulse inertial propulsion system from the energy point of view, the amount of momentum and the momentum of the force. As a result of the theoretical studies performed, the possibility and principle of operation of a mechanical impulse inertial propulsion system for closed systems have been shown, which, in particular, can be used for accelerating spacecraft during interplanetary flights, as well as for space shuttles with wings. It should be noted that only practical experimental research in space can remove the status of a pseudoscientific concept from the inertial propulsion system.